Pelatihan Digital Marketing Berbasis Smartphone Untuk Membangun Kemandirian Ekonomi Pada Komunitas Tuli Gresik - Supriyanto, Supriyanto; Hafid Kholidi Hadi; Ima Kurrotun Ainin; Hitta Alfi Muhimmah; Muh Ariffudin Islam (Abimanyu : Jornal of Community Engagement, 2025)
Gresik Deaf Community (Kotugres) is a community of young and productive deaf people who need to receive smartphone-based digital marketing training to support their economic independence. This training can also be used as a strategy to empower Kotugres from unfavorable conditions such as negative stigma from society, discrimination, neglect and even economic and social marginalization. Kotugres' products need to be marketed digitally after the manual/offline business process stagnates due to changes in people's mindsets that are starting to abandon offline shopping habits and tend to increase interest in online shopping, especially the post-COVID-19 pandemic recovery situation which has not yet subsided 100% makes smartphone-based digital marketing platforms increasingly needed and favored by the community. The method of implementing activities consists of the stages of need assessment, program planning, program implementation, and program evaluation. The results of the implementation of activities are significant positive impacts in the form of increased interest, knowledge and abilities of Kotugres members in carrying out smartphone digital marketing. To ensure the continuity of the impact of training activities, cooperation is needed with partners who can continue the implementation of the program continuously to maintain the long-term impact of the training.